PENGEMBANGAN ANGKET KESULITAN SISWA DALAM MELAKSANAKAN PRAKTIK KERJA KELOMPOK PADA MATA PELAJARAN IPAS KELAS V SD DI PALANGKARAYA: Pengembangan - Damayanti, Dewi Damayanti; Safitri, Widya Safitri; Septiani, Pebriana Septiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This is a research and development study using the ADDIE model. Data collection techniques used include interviews, observation, and documentation. The subjects of the research are fifth-grade students with 18 students in the limited test and 71 students in the expanded test. Data analysis techniques used include quantitative and qualitative analysis. The research results show that the student difficulty questionnaire has (1) theoretical validity in the content section of 4,15 with a valid category, the construction section of 5,00 with a very valid category, the language section of 4,1 with a valid category, (2) empirical validity in the limited trial of 23 valid items and the expanded trial of 26 valid items, (3) reliability in the student difficulty questionnaire in the limited trial of 0,90 and the expanded trial of 0,89, (4) the practicality test of the questionnaire shows practical results so that it is feasible to use as a measuring tool for student difficulties in carrying out group work practices in fifth grade elementary school.